Perancangan Sistem Informasi Pendaftaran Hak Cipta - Sukardi, Aldy; Trisnawarman, Dedi; Perdana, Novario Jaya (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
This research aims to design an information system that can simplify the copyright registration process. The system design method used is a prototype model, which consists of communication stages, rapid planning, design modeling, prototype formation, and evaluation. The design results show that the copyright registration information system can provide features such as submitting applications, document management, status monitoring, and notifications. In addition, this system also applies automation in various processes, such as processing application data and sending notifications to applicants, which reduces the need for manual intervention. Through a prototyping approach, the system can be continuously refined based on user feedback to ensure it meets requirements. This system has succeeded in increasing the efficiency, transparency and accessibility of the copyright registration process, while reducing the possibility of errors that can occur in manual processes. Thus, automation plays an important role in speeding up and simplifying the entire copyright registration process.